Enhancing the mechanical properties of 3D printed polylactic acid using nanocellulose. Issue 8 (2nd June 2020) - Ambone, Tushar; Torris, Arun; Shanmuganathan, Kadhiravan
Abstract: We report here a systematic investigation of the mechanical properties of polylactic acid (PLA) processed by fused filament fabrication (FFF) 3D printing vs PLA processed by compression molding. Our results show that the tensile strength and modulus of FFF‐PLA is 49% and 41% lower, respectively, than compression molded samples of PLA. We also demonstrate here an approach to augment the mechanical properties of 3D printed PLA using nanocellulose. Incorporation of a small quantity (1 wt%) of cellulose nanofibers (CNF) was found to enhance the tensile strength and modulus of 3D printed PLA by 84% and 63%, respectively. X‐ray microtomography was used to probe the morphology of 3D printed PLA and PLA/CNF composites. 3D printed PLA/CNF composites had significantly lesser voids as compared to neat 3D printed PLA. Differential scanning calorimetry study revealed that CNF can accelerate the nucleation and crystallization of 3D printed PLA leading to enhanced crystallinity. The thermal stability of 3D printed PLA/CNF composites was not compromised by the addition of CNF. The enhanced mechanical properties of 3D printed PLA/CNF composites can be ascribed to higher crystallinity and lesser defects. Abstract :